2023
DOI: 10.1021/acsmacrolett.3c00276
|View full text |Cite
|
Sign up to set email alerts
|

Ionic-Liquid-Mediated Deconstruction of Polymers for Advanced Recycling and Upcycling

Abstract: Ionic liquids (ILs) are a promising medium to assist in the advanced (chemical and biological) recycling of polymers, owing to their tunable catalytic activity, tailorable chemical functionality, low vapor pressures, and thermal stability. These unique physicochemical properties, combined with ILs' capacity to solubilize plastics waste and biopolymers, offer routes to deconstruct polymers at reduced temperatures (and lower energy inputs) versus conventional bulk and solvent-based methods, while also minimizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 177 publications
0
4
0
Order By: Relevance
“…194 New types of solvents offer new opportunities, such as ionic liquids whose chemical design can be tailored to target catalytic performance, decomposition temperatures, and polymer solubilities for specific deconstruction applications. 30 These studies confirmed that solvent effects on depolymerization are an important factor, which requires more in-depth studies with green solvents being prioritized. The high costs and challenges in handling high dilution needs to be addressed.…”
Section: Closing Remarksmentioning
confidence: 68%
See 1 more Smart Citation
“…194 New types of solvents offer new opportunities, such as ionic liquids whose chemical design can be tailored to target catalytic performance, decomposition temperatures, and polymer solubilities for specific deconstruction applications. 30 These studies confirmed that solvent effects on depolymerization are an important factor, which requires more in-depth studies with green solvents being prioritized. The high costs and challenges in handling high dilution needs to be addressed.…”
Section: Closing Remarksmentioning
confidence: 68%
“…24,25 Catalysis and processes such as temperature-gradient thermolysis are paving the way for upcycling of polyolefins. 26–28 Investigations into different solvents, 29,30 and conditions to depolymerize vinyl polymers 31 are also among the forefront of recent progresses. Developing new polymers to replace current ones also have many challenges to be addressed, chief among them is finding materials that have comparable stability and mechanical performances to existing commodity polymers and achieving economic feasibility of scaling up.…”
Section: Introductionmentioning
confidence: 99%
“…107 Strategies for separating IL monomers to achieve recyclability, reduced viscosities of ILs at high temperatures, and chemical arguments about increased thermal stability are crucial points for effective deconstruction of polymers, which resolve pending issues regarding ILs and facilitate their application on a commercial scale. 108 As most Bio-ILs employ highly basic anions (such as deprotonated amino acids), it is likely that their thermal stability will be lower than that of traditional ILs. 109…”
Section: Production Of Renewable Commodities From Il Treated Ligninmentioning
confidence: 99%
“…Ionic liquids (ILs) composed of organic cations and organic/inorganic anions have been emerging as a kind of functional materials and applied in various chemical processes due to their unique properties 25 28 . It was reported the basic ILs (e.g., [EMIm][AcO]) could accomplish PHB decomposition into crotonic acid 29 , 30 . Furthermore, the ILs with halide anions have been widely employed as solvents or catalysts in various chemical reactions.…”
Section: Introductionmentioning
confidence: 99%